Wacana Penghancuran Diri Perempuan sebagai Bentuk Perlawanan Stereotip dalam Sagra (2023) karya Oka Rusmini - Komang Rama Juliartha Komang Rama Juliartha; Juniartha I Wayan; I Gusti Bagus Wahyu Nugraha Putra I Gusti Bagus Wahyu Nugraha Putra; Dewa Gede Bambang Erawan Dewa Gede Bambang Erawan (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2026)
This research aims to analyze the discourse and meanings of acts of self-destruction as representations of resistance to oppressive stereotypes imposed on female characters in the short story compilation Sagra. The study employs a social constructivist approach in literary studies to explore the correlation between the discourse and meaning in actions that challenge stereotypes of women. The focus of this research is the discourse of resistance to socially constructed stereotypes of women, particularly those related to women’s bodies. These stereotypes are manifested through acts of self-destruction that are directly connected to women’s bodies. The study adopts a qualitative research design using literary analysis methods. Library research and close reading methods, supported by systematic note-taking techniques, are used to identify the relationship between discourse and the meanings of acts of self-destruction as forms of resistance to stereotypes. The analysis is grounded in Fairclough’s Critical Discourse Analysis and Mead’s theory of Symbolic Interactionism. The findings indicate that acts of self-destruction performed by female characters are not expressions of despair or surrender to oppression, but rather function as coping mechanisms to assert ownership over their bodies. These acts are interpreted both literally and metaphorically, particularly in relation to self-actualization. Ultimately, the contribution of this research is to offer a new perspective on the discourse of women’s self-destruction within the context of patriarchy. Rather than interpreting self-destruction as a form of despair, this act can be understood as a form of resistance that voices women’s rights over the ownership of their own bodies.